Generalized inverse operators: with an introduction to Fredholm boundary-value problems - Boichuk, Alexander Andreevych; Samoilenko, Anatolii M; Malyshev, Peter V (Inverse and ill-posed problems series, 2016)
The book is devoted to the theory of generalized inverses of operators in a Banach space and its applications to linear and weakly nonlinear boundary-value problems for various classes of functional-differential equations, including systems of ordinary differential and difference equations, systems of differential equations with delay, systems with impulse action, and integro-differential systems.